Ascorbic acid intake during pregnancy - Podolska, Kristina; Mazankova, Dana; Goboova, Maria; Vano, Ivan (Biomedical papers, 2023)
The continuing global increase in allergic conditions and diseases in children is now a serious public health and scientific issue. Amongst other concerns is the maternal antenatal diet as intake of essential nutrients. Even small deficits in essential vitamin C can permanently impair the developing brain for example. In this article, we first review ascorbic acid deficiency in different organs of both mother and foetus. However, major emphasis is on the importance of vitamin C in foetal immunity with studies showing an inverse relationship between maternal intake of fresh fruit and vegetables and allergic conditions in childhood, inter alia. Other review results are included.
Keywords: pregnancy; ascorbic acid; ascorbic acid deficiency; foetal health